Pelatihan Penulisan Surat Lamaran Kerja dan Daftar Riwayat Hidup Berbasis Canva untuk Meningkatkan Kesiapan Kerja Siswa SMK NU 2 Glagah - Abdullah Syarofi; Nadya Afdholy; Eddy Sugiri (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
A limited understanding of the structure and proper format of job application letters and curricula vitae often hinders vocational high school students from entering the workforce. To address this issue, the authors conducted a community service program in the form of training for 41 twelfth-grade students at SMK NU 2 Glagah, where many students were found to make errors in preparing job application letters and curricula vitae. The program employed the Participatory Action Research (PAR) approach, which combines action and reflection through a cyclical process to promote learning and continuous improvement. The training aimed to enhance students' knowledge and skills in writing job application letters and curricula vitae using Canva. The implementation consisted of four stages: delivering instructional materials, introducing the operation of Canva, guiding students in preparing job application letters and curricula vitae, and conducting evaluation and dissemination of the results. The findings showed that: (1) in terms of the structure and format of job application letters and curricula vitae, 10 students achieved an excellent rating, 21 received a good rating, and 10 were rated fairly good; (2) regarding sentence construction in job application letters prepared using Canva, 4 students achieved an excellent rating, 12 received a good rating, and the remaining 25 were rated fairly good; and (3) regarding the selection of Canva design templates, 14 students achieved an excellent rating, 14 received a good rating, and 13 were rated fairly good. Overall, the training improved students' ability to use Canva and prepare job application letters and curricula vitae effectively. Students' creativity in writing job application letters can be further enhanced through continuous writing practice both at school and at home, supported by regular reading activities.